The Antigastric Cancer Activity of San Leng Powder Extract Induces Apoptosis in Balb/C Bearing-SGC-7901 Mice. (8th May 2017) - Yu, Chen; Ji, Ai-Jun; Lu, Jian-Wei; Liu, Shi-Jia; Sun, Yu
Abstract : San Leng powder extract has been used as medicinal compound for the prevention and treatment of cancers. The antitumor activity of SLPE was determined by treating BALB/C mice harboring a human gastric cancer xenograft with SPLE for 17 days. Mice were also treated with fluorouracil (5-Fu, 25 mg/kg) or a combination of SLPE and 5-Fu. Our results indicate that the inhibition of tumor growth by SLPE might be due to a block in the cell cycle and the induction of apoptosis. These results suggest that SLPE might be useful in the treatment of gastric cancer.